Further Observations on Whether Host Immunodepression is Associated with Tumour Growth in Mice - Rees, Jennifer A. (Nature Publishing Group, 1971)
In order to investigate whether the presence of a tumour was associated with immunodepression in the host, spleen cells from parent line animals with tumours were injected intravenously into F(1) hybrids, half of which carried the same tumour. Further groups of F(1) hybrid with and without the tumour received spleen cells from non-tumour bearing parent line animals. The G.V.H. reactions induced in the four groups of F(1) hybrid were compared and no significant differences were found. This was true in separate experiments, involving two mammary carcinomata and a 3-methylcholanthrene induced sarcoma, wherein the period of tumour growth in the parent line donor and F(1) hybrid recipient was varied.